Sensitive Anodic Stripping Voltammetric Copper Ions Determination Performed in Double Deposition and Double Stripping Steps System for Real Water Samples Analysis. Issue 6 (2nd March 2020) - Gęca, Iwona; Ochab, Mateusz
Abstract: The article reports on utilization of double deposition and stripping steps for increasing sensitivity of Cu(II) determination by anodic stripping voltammetry (ASV) at two lead film working electrodes. A significant preconcentration of copper was achieved thanks to utilization of a simple design of four electrodes system that gives possibility to perform one measurement cycle consisting of two deposition and two stripping steps. Due to the fact that deposition step is doubled, the concentration of Pb(II) needed to lead film electrodes formation was significantly reduced as compared to traditional procedures using three electrodes system. The analytical procedure of Cu(II) determination was optimized. The experimental factors: supporting electrolyte's pH and its concentration, lead ions concentration, potential and time of deposition at both working electrodes were studied. The Cu(II) peak current was linearly dependent on its concentration from 5×10 −10 to 2×10 −8 mol L −1 (deposition time of 270 and 160 s at the first and the second working electrode, respectively). The obtained detection limit for copper ions determination was 2.1×10 −10 mol L −1 . The described procedure was validated by analysis of two water certified reference materials. The described procedure was also utilized for real water sample analysis. Abstract :